O Gato de Cheshire quântico como um fenômeno de interferência - Raul Correa Silva (2015)
Based on the concept of weak measurements, in 2013 Aharonov et al. proposed an experiment in which, according to their interpretation of the predicted results, a photon and its circular polarization were spatially separated, naming this phenomenon quantum Cheshire Cat [1]. This name is after a character in Lewis Carrolls novel Alice In Wonderland, the Cheshire Cat a cat whose grin can exist without the animal itself. Denkmayr et al., in 2014, claimed they realized experimentally the quantum Cheshire Cat, separating a neutron from its intrinsic magnetic moment [3]. We show how both results follow from interference effects, and thus the conclusion that a particle is separated from one of its intrinsic properties is not a necessary one. Making use of mostly undergraduate level quantum mechanics, we rule out the apparent paradox of the quantum Cheshire Cat.